Safe haven - Sparks, Nicholas (New York : Grand Central Pub., 2010)
When an enigmatic stranger shows up out of the blue, the folks of sleepy Southport become suspicious of her past.
1979
Keywords: 0 Female friendship -- North Carolina -- Fiction; 0 Cancer -- Patients -- Fiction; 0 Man-woman relationships -- North Carolina -- Fiction; 0 Widowers -- Fiction; 0 Southport (N.C.) -- Fiction; 7 Love stories